Compositional Changes during Papaya Fruit Ripening - Shattir, Adil E.; Goukh, Abu-Bakr A. Abu- (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to investigate compositional changes during ripening of ‘Baladi’, ‘Ekostika I’ and ‘Ekostika II’ papaya fruit cultivars at 20 ±1 ⁰C and 85% - 90% relative humidity. The fruits of the three cultivars exhibited a typical climacteric pattern of respiration with peak of respiration of 82, 92 and 98 mg CO 2 / kg-hr, reached after 10 days in the three cultivars, respectively. Weight loss, total soluble solids (TSS), total sugars and ascorbic acid content progressively increased during ripening of the three papaya cultivars. More increase in TSS and total sugars was observed after the climacteric peak of respiration. Fruit tissue firmness and total phenolic compounds decreased continuously during ripening in the three cultivars. Reducing sugars, total protein and titratable acidity steadily increased to reach a peak, which coincided with the climacteric peak of respiration, and subsequently decreased afterwards. The local ‘Baladi’ cultivar had a lower respiration rate, more firm and less weight loss during ripening, which may indicate a longer shelf-life than the other two introduced cultivars. On the other hand, the introduced cultivars were higher in TSS, total and reducing sugars and ascorbic acid content and lower in titratable acidity and phenolic compounds, which may reflect a better eating quality.